A principal component analysis of postinjury viscoelastic assays: clotting factor depletion versus fibrinolysis - Chin, Theresa L. (2014)
INTRODUCTION: The mechanisms driving trauma-induced coagulopathy (TIC) remain to be defined and its therapy demands an orchestrated replacement of specific blood products. Thrombelastography (TEG) is a tool to guide the TIC multicomponent therapy. Principal component analysis (PCA) is a statistical approach that identifies variable clusters, thus, we hypothesize that PCA can identify specific combinations of TEG-generated values that reflect TIC mechanisms. METHODS: Adult trauma patients admitted from September 2010 to October 2013 for whom a massive transfusion protocol was activated were included. Rapid TEG values obtained within the first 6 hours postinjury were included in the PCA analysis. PCA components with an eigenvalue >1 were retained, and, within components, variable loadings (equivalent to correlation coefficients)>|60| were considered significant. Component scorings for each patient were calculated and clinical characteristics of patients with high and low scores were compared. RESULTS: Of 98 enrolled patients, 67% were male and 70% suffered blunt trauma. Median age was 41 years (IQR:28-55) and median Injury Severity Score was 31.5 (IQR: 24-43). PCA identified three principal components (PC) that together explained 93% of the overall variance. PC1 reflected global coagulopathy with depletion of platelets and fibrinogen whereas PC3 indicated hyperfibrinolysis. PC2 may represent endogenous anticoagulants such as the activation of protein C. CONCLUSIONS: PCA suggests depletion coagulopathy is independent from fibrinolytic coagulopathy. Furthermore, the distribution of mortality suggests that low levels of fibrinolysis may be beneficial in a select group of injured patients. These data underscore the potential of risk for concurrent presumptive treatment for preserved depletion coagulopathy and possible fibrinolysis.